Design and assessment of a personal breathalyzer intervention to support responsible drinking. Issue 137 (May 2020) - Min, Aehong; Lee, Daehyoung; Gao, Gege; Jeong, Stella; Shih, Patrick C.
Highlights: Students enjoy using breathalyzers to monitor their health and safety. Students are not worried by potential stigma related to breathalyzer use in public. Social context must be considered when designing interventions for responsible drinking. The study resulted in design examples that could facilitate safe drinking culture. Abstract: This study explores current drinking practices and attitudes of college students and design opportunities for encouraging safe and responsible drinking behaviors in this population. With 86 participants in total, we conducted surveys, interviews, and a two-week user study that involved the use of BACtrack Mobile Pro, an FDA-approved personal breathalyzer which can be connected to a smartphone app. For the user study, we conducted pre-study and weekly surveys, user experience evaluations, and in-depth post-study interviews with 24 college students who regularly consume alcohol. We identified and compared two groups of participants based on the Alcohol Use Disorders Identification Test (AUDIT), which is a screening test for risky drinking behaviors. We propose a new system, smartphone app user interface, and experiences based on our findings. Finally, we discuss the role and implications of future technological interventions that could lead to safe and responsible drinking behaviors among college students.